Gambaran Penerapan Pola Asuh Orang Tua dengan Anak Attention Deficit/Hyperactivity Disorder - Paralea, Diandra; Handayani, Penny (Fakultas Psikologi Universitas Sanata Dharma, 2024)
This research study delves into the parenting styles employed by parents of children with Attention Deficit Hyperactivity Disorder (ADHD). ADHD is a neurodevelopmental disorder characterized by inattention, hyperactivity, and impulsivity, potentially impacting a child's social, academic, and professional functioning. The research method used is qualitative. The study involved three pairs of parents cohabiting with their children aged 6-11 years old who have been diagnosed with ADHD by a specialist. The Parenting Styles and Dimensions Questionnaire (PSDQ) was employed to categorize the parenting styles of each couple. Screening results were further analyzed qualitatively, and semi-structured interviews were conducted to gather qualitative data. The findings revealed that parents do not adhere to a single parenting style, exhibiting varied responses and employing different styles depending on the situation and specific conditions. Mothers tend to be more involved in their child's daily activities, actively implementing strategies to manage ADHD symptoms, while fathers are more involved in disciplining their children through punishments aimed at promoting discipline.